Peran Psikologi Dakwah dalam Mengatasi Kekerasan Seksual pada Santri dan Relasi Kuasa Kyai - Wulandari, Uli Mardiyah; Yunita, Fita (IAINU Kebumen, 2025)
Sexual violence in Islamic boarding schools is a very serious problem and has a negative impact on the mental and psychological health of students. The Islamic boarding school environment, which should be a safe and educational place, has instead become a place where harassment occurs, especially because of the power relations between the kyai and the students. The purpose of this study is to examine the role of preaching psychology in overcoming sexual violence with an approach that combines the principles of psychology and Islamic values. This research method uses qualitative research with data collection methods and library studies. The results of the study indicate that preaching psychology plays an important role in providing psychological and spiritual assistance to harassment that occurs in the Islamic boarding school environment. This approach also helps change the unequal power relations between the kyai and the students, and encourages the prevention of sexual violence through strengthening moral and ethical values. Thus, preaching psychology becomes an effective strategy in overcoming and preventing sexual violence in the Islamic boarding school environment, as well as in supporting psychological recovery and empowerment of students.